Dampak Pengetahuan, Sikap dan Burnout Terhadap Perilaku Pencegahan Covid-19 Pada Tenaga Kesehatan di Fasilitas Kesehatan Primer Kota Serang - Lao, Alexsandro I.S.; Di Margt, Constello; Temaluru, Yohanes (Jurusan Biologi FMIPA Universitas Cenderawasih, 2023)
The COVID-19 pandemic has escalated into a global outbreak, with the number of confirmed positive cases reaching hundreds of millions worldwide in March 2023. Its impact extended beyond the healthcare sector, affecting the economy, social culture, and businesses. Healthcare workers at primary healthcare facilities, particularly at Puskesmas, faced a high risk of COVID-19 exposure, necessitating appropriate knowledge, behavior, and attitudes towards virus transmission. Therefore, Puskesmas, as a primary healthcare facility in Indonesia, became the focus of this research to understand and address the impacts of COVID-19 on healthcare workers and the community. Amidst the COVID-19 pandemic, understanding the factors influencing preventive behavior against COVID-19 among healthcare workers was crucial. However, there was a lack of research on the specific factors affecting COVID-19 prevention behavior in Indonesia. Hence, the objective of this study was to investigate the impact of knowledge, attitude, and burnout on COVID-19 prevention behavior among healthcare workers in healthcare facilities in Serang. Partial Least Squares Structural Equation Modeling (PLS-SEM) was utilized to analyze empirical data obtained through simple random sampling. The study collected responses from 181 eligible participants through an online questionnaire. The research findings revealed that the three variables, namely knowledge, attitude, and burnout, had positive and significant impacts on COVID-19 prevention behavior. Among the variables, knowledge had the most substantial direct impact on preventive behavior, followed by attitude and burnout. Notably, burnout negatively influences COVID-19 prevention behavior. This study demonstrated that knowledge, attitude, and burnout significantly influence COVID-19 prevention behavior among healthcare workers, indicating potential applications for healthcare facility management. PLS-SEM model in this research showed moderate predictive accuracy and relevance, suggesting possibilities for further development in future studies. The findings had managerial implications and offered recommendations for future researchers. Key words: attitude; awareness; behavior; burnout; preventive.